2022
DOI: 10.3389/fimmu.2022.900755
|View full text |Cite
|
Sign up to set email alerts
|

Csf2ra deletion attenuates acute lung injuries induced by intratracheal inoculation of aerosolized ricin in mice

Abstract: Specific therapeutics are not available for acute lung injury (ALI) induced by ricin toxin (RT). Inhibiting the host immune response in the course of pulmonary ricinosis is hypothesized to be of benefit and can be achieved by impairing granulocyte-macrophage colony-stimulating factor (GM-CSF) signaling, thereby reducing the pro-inflammatory response to exogenous foreign body invasion. However, it is unknown whether mice with impaired GM-CSF signaling can survive after RT inhalation. To test this, colony stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Our experimental results showed that LPS activates NF-κB signaling pathway by promoting the phosphorylation of IκB and p65, which is in consistence with the relevant reports ( 40 , 68 ). LETX-VI pretreatment inhibits LPS-induced NF-κB signaling pathway activation by suppressing the phosphorylation of IκB and p65 and thus inhibits LPS-induced inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…Our experimental results showed that LPS activates NF-κB signaling pathway by promoting the phosphorylation of IκB and p65, which is in consistence with the relevant reports ( 40 , 68 ). LETX-VI pretreatment inhibits LPS-induced NF-κB signaling pathway activation by suppressing the phosphorylation of IκB and p65 and thus inhibits LPS-induced inflammation.…”
Section: Discussionsupporting
confidence: 92%